The Effect of Whole Blood and Bone Marrow with the Addition of Pyrimidine-2,4(1h,3h)-dione Thietanyl Derivatives on Free Radical Oxidation - Meshcheryakova, Svetlana; Kayumova, Aliya; Kang, Yang; Shumadalova, Alina; Vinogradova, Yulia; Khuzin, Dinislam; Ziyakaeva, Klara; Kiseleva, Olga; Gabdulkhakova, Irina; Beylerli, Ozal; Gareev, Ilgiz; Sufianov, Albert; et al. (Current Medicinal Chemistry, 2023)
Background: It is relevant to study the general patterns and identify non-specific mechanisms of body protective and adaptive reactions violation, which can lead to the various pathological processes and develop principles for the correction of these disorders. One of the therapy and prevention directions is the search for new medicines. In recent years, new derivatives of pyrimidine bases have been synthesized and studied. Pyrimidine-based medicines have a membrane-stabilizing and immunomodulatory effect and can normalize metabolic disorders and increase the oxidative activity of leukocytes. Disruption of the free radical oxidation processes, the generation of reactive oxygen species and lipid peroxidation, including in whole blood and bone marrow, has gained importance in recent years. Methods: Each reaction was monitored by thin layer chromatography. 1H, 13C, and 15N NMR spectra were recorded (chemical shifts were expressed as δ-values). We studied the effect of 6-methyl-3-(thietan- 3-yl)pyrimidine-2,4(1H,3H)-dione on the generation of reactive oxygen species (ROS) in the whole blood and bone marrow using the study of whole blood spontaneous and stimulated chemiluminescence (CL). CL methods make it possible to quickly and easily assess the studied material (whole blood, bone marrow) effect on free radical oxidation. Using CL methods, it is possible to reveal the presence of medicines' pro- or antioxidant properties, opening up new possibilities in the search for substances with antioxidant properties and comparing their activity. Results: Alkylation of 6-methylpyrimidine-2,4(1H,3H)-dione by 2-chloromethylthiirane in protic solvents in the presence of alkali leads to the formation of an N-thietane derivative. NMR spectroscopy showed that 6-methylpyrimidine-2,4(1H,3H)-dione was alkylated at position 3. The oxidation reactions of N-(thietan-3-yl)pyrimidine-2,4(1H,3H)-dione were studied, and it was determined that, depending on the excess of the oxidizing agent and the duration of the process, N-(1-oxothietan-3-yl)- or N-(1,1– dioxothietan-3-yl)pyrimidine-2,4(1H,3H)-diones were formed. The effects of free radical oxidation processes of new biologically active pyrimidine-2,4(1H,3H)-diones were studied. Conclusion: New pyrimidine-2,4(1H,3H)-diones increase the general adaptive capabilities of the body and have protective effects in extreme conditions.
Keywords: free radical oxidation